DYNAMICS OF GLOBAL ECONOMICS AND WOMEN “IMPOVERISMENT”: WHAT RELIGION TO DO WITH? - Misbah Zulfa Elizabeth (Analisa: Journal of Social Science and Religion, 2017)
Although it was stated that nowadays is “the third wave”, the time for minority, included women, for taking part in so many public activities, it did not mean that women can do as they really want to do to express their capacities as well as capabilities in their life cyrcle. Applying literature study it was revealed that although women can choose their activities, domestic or public, but the fact showed that there are so much cultural burden that women may encounter in the both sphere of their life. Women impoverishment is the term that seemed appropriate to the condition that are the women facing in choosing their life, both in domestic and public sphere because of the domination of globalization. This article showed that factually women took part in most of public sectors but generally women posited in lower level of access, participation, and respect. By reflective method, even religion treated women as other social processes. There are some biases view on women disseminated in religious spreading that effected in the sustainability of the gender inequality in society context.